Structural Changes in Mortgage Fund Flows: Discussion - Pratt, Richard T.; Martin, Preston (Journal of Finance, 1968)
Richard T. Pratt, Preston Martin, Structural Changes in Mortgage Fund Flows: Discussion, The Journal of Finance, Vol. 23, No. 2, Papers and Proceedings of the Twenty-Sixth Annual Meeting of the American Finance Association Washington, D.C. December 28-30, 1967 (May, 1968), pp. 379-387